Improved thin sheet aluminum-copper-lithium alloy
Patent Information
- Application Number
- JP2024544637
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-28
- Filing Date
- 2023-01-26
- Publication Date
- 2025-02-19
Smart Images

Figure 2025504927000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to thin sheets made of an aluminium-copper-lithium alloy intended for aeronautical and space structures, in particular for fuselage sheeting applications, and more particularly to such products, their manufacturing and use methods. [Background technology]
[0002] There is a continuing research effort to develop materials that can reduce the weight of high performance aircraft structures while increasing their effectiveness. In this regard, aluminum-lithium (AlLi) alloys are highly advantageous because lithium can reduce the density of aluminum by 3% and increase the elastic modulus by 6% per weight percent of added lithium.
[0003] EP 1891247 discloses a low density aluminum-based alloy useful in aircraft construction for fuselage sheet applications, having high mechanical strength, high toughness and high corrosion resistance, containing, by weight percent, 2.7-3.4 Cu, 0.8-1.4 Li, 0.1-0.8 Ag, 0.2-0.6 Mg, and elements such as Zr, Mn, Cr, Sc, Hf, Ti, or combinations of these elements, in amounts, by weight percent, of Zr: 0.05-0.13, Mn: 0.05-0.8, Cr and Sc: 0.05-0.3, Hf: 0.05-0.5, and Ti: 0.05-0.15. The amounts of Cu and Li are determined according to the formula Cu(wt%)+5 / 3Li(wt%)<5.2.
[0004] US Patent 5,455,003 describes a method for producing Al-Cu-Li alloys with improved mechanical strength and toughness at cryogenic temperatures, especially by proper processing and aging. The patent specifically recommends a composition in weight percent of Cu=3.0-4.5, Li=0.7-1.1, Ag=0-0.6, Mg=0.3-0.6, and Zn=0-0.75. US Patent 5,455,003 encourages the development of non-recrystallized products and the use of Zr and Ti additions to obtain the desired properties under cryogenic conditions.
[0005] Fuselage sheets may be stressed in multiple directions, and there is a strong demand for isotropic thin sheets with high properties that balance mechanical strength in the L and TL directions with toughness in the LT and TL directions. Moreover, it has been recognized that thin sheets obtained with an alloy having high properties at a certain thickness, e.g., 4 mm, may in some cases have less high or anisotropic properties at other thicknesses, e.g., 2.5 mm. The use of different alloys at different thicknesses is often not industrially advantageous, and an alloy that can achieve high and isotropic properties regardless of thickness would be highly advantageous.
[0006] EP 1966402 describes an alloy containing 2.1-2.8% by weight Cu, 1.1-1.7% by weight Li, 0.1-0.8% by weight Ag, 0.2-0.6% by weight Mg, 0.2-0.6% by weight Mn, Fe and Si in amounts less than 0.1% by weight each, and unavoidable impurities with a content of less than 0.05% by weight each and less than 0.15% by weight in total, which is substantially free of zirconium and is particularly suitable for obtaining recrystallized thin sheets.
[0007] WO 2016 / 051099 describes a sheet having a thickness of 0.5-9 mm and having an essentially recrystallized grain structure made of an aluminium-based alloy containing 2.8-3.2% by weight of Cu, 0.5-0.8% by weight of Li, 0.1-0.3% by weight of Ag, 0.2-0.7% by weight of Mg, 0.2-0.6% by weight of Mn, 0.01-0.15% by weight of Ti, Zn in an amount of less than 0.2% by weight, Fe and Si in an amount of less than 0.1% by weight each, and unavoidable impurities in a content of less than 0.05% by weight each and less than 0.15% by weight in total, obtained by a process including casting, homogenizing, hot rolling and optionally cold rolling, solution treatment, quenching and ageing.
[0008] Thin sheets are required that have high yield strength (to resist buckling) as well as high plane strain toughness, specifically high apparent stress intensity factor values at break (Kapp) and high Δaeff_max values, where Δaeff_max represents the crack extension at the end of the R-curve, valid according to the ASTM E561-20 standard.
[0009] WO2016 / 051099 discloses R-curve data in Figures 1 and 2. These R-curves are not limited to only the effective points. The inventors have confirmed that the disclosure and examples of WO2016 / 051099 do not allow Δaeff_max values of more than 80 mm to be obtained.
[0010] The R-curve test is a widely recognized means for characterizing toughness properties. The R-curve represents the change in the critical effective stress intensity factor for crack propagation as a function of the effective crack extension under increasing monotonic stress. This curve makes it possible to determine the critical load for unstable fracture for any configuration relevant for cracked aircraft structures. The values of the stress intensity factor and the crack extension are effective values as defined in the ASTM E561-20 standard. A commonly used conventional analysis of tests carried out on panels with a central crack gives the apparent stress intensity factor at fracture (Kapp). This value does not necessarily vary in a meaningful way with the length of the R-curve. However, the length of the R-curve (i.e. the maximum crack extension Δaeff_max of the curve) is itself an important parameter for the design of fuselages, in particular for panels containing fixed stiffeners. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] European Patent No. 1891247 [Patent Document 2] U.S. Patent No. 5,455,003 [Patent Document 3] European Patent No. 1966402 [Patent Document 4] International Publication No. 2016 / 051099 Summary of the Invention
[0012] A first object of the present invention is a thin sheet less than 12.7 mm thick having an essentially recrystallized grain structure made of an aluminium-based alloy containing, in weight percent, 2.5-3.5% Cu, 0.7-0.9% Li, 0.3-0.5% Mg, 0.2-0.5% Mn, 0.25-0.65% Zn, 0.01-0.15% Ti, 0-0.07% Ag, Fe and Si in an amount of less than 0.1% each, and unavoidable impurities with a content of less than 0.05% each and less than 0.15% in total by weight, the remainder being aluminium.
[0013] A second subject of the invention is a method for producing thin sheets made of an aluminum alloy and having a thickness of less than 12.7 mm, comprising the steps of: a) by weight percent: 2.5-3.5% Cu, 0.7-0.9% Li, 0.3-0.5% Mg, 0.2-0.5% Mn, 0.25-0.65% Zn, 0.01 to 0.15% Ti, 0-0.07% Ag, Fe and Si in amounts not exceeding 0.1% each, and incidental impurities in amounts not exceeding 0.05% each and not exceeding 0.15% in total, the remainder being aluminum; preparing a liquid metal bath to obtain an aluminum alloy; b) casting a plate from said liquid metal bath; c) homogenizing the plate at a temperature of 480°C to 535°C; d) rolling said plate by hot rolling and optionally cold rolling into a sheet having a thickness of less than 12.7 mm, preferably between 0.5 mm and 9 mm; e) subjecting the sheet to solution treatment at a temperature of 450°C to 535°C and quenching; f) subjecting the sheet to controlled tension with a permanent deformation of 0.5-5%; g) carrying out an ageing process which involves heating at a temperature of 130-170°C, preferably 150-160°C, for a period of 5-100 hours, preferably 10-60 hours; This is the method.
[0014] Yet another subject of the invention is the use of a thin sheet according to the invention or obtainable according to the method of the invention for a structural element of a fuselage. [Brief description of the drawings]
[0015] [Figure 1] 4 represents the variation of the tensile elastic limit Rp0.2 as a function of time of ageing at 155° C. for different sheets according to Example 1. [Diagram 2] 1 represents the compromise between Rp0.2-TL and Kapp(TL) for the sheets tested in Examples 1 and 3. [Diagram 3] 1 represents the compromise between Rp0.2-TL and Δaeff_max for the sheets tested in Examples 1 and 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Unless otherwise stated, all indications regarding the chemical composition of the alloys are expressed as weight percentages based on the total weight of the alloy. The designations of the alloys are made in accordance with the Aluminum Association rules known to those skilled in the art. The definitions of metallurgical states are given in the European standard EN515-2017.
[0017] Within the scope of the present invention, an essentially non-recrystallized grain structure means a grain structure with a recrystallization rate at half thickness of less than 30%, preferably less than 10%, and an essentially recrystallized grain structure means a grain structure with a recrystallization rate at half thickness of more than 70%, preferably more than 90%. The recrystallization rate is defined as the percentage of the surface area on a metallographic cross section that is occupied by recrystallized grains. The grain size is measured according to the ASTM E112-2013 standard.
[0018] Unless otherwise specified, the static properties, i.e. the ultimate breaking strength Rm and the tensile elastic limit R p0.2 and the breaking elongation A are determined by tensile tests in accordance with the EN 6892-1-2019 standard, the locations where the pieces are taken and their orientation are defined by the EN 485-1-2016 standard.
[0019] A curve showing the effective stress intensity factor as a function of the effective crack extension, known as the R-curve, is determined according to the ASTM E 561-20 standard. The critical stress intensity factor KC, in other words the extension factor that makes the crack unstable, is calculated from the R-curve. The stress intensity factor KC0 is also calculated by assigning the initial crack length at the beginning of the monotonic load to the critical load. These two values are calculated for the specimen of the desired geometry. Kapp represents the coefficient KC0 corresponding to the specimen used to perform the test of the R-curve. Keff represents the coefficient KC corresponding to the specimen used to perform the test of the R-curve. Δaeff_max represents the crack extension of the last effective point of the R-curve that is valid according to the ASTM E561-20 standard. The last effective point is obtained at the time of abrupt fracture of the specimen or, in some cases, at the time when the stress on the uncracked ligaments averages above the elastic limit of the material. Unless otherwise stated, the crack size at the end of the fatigue pre-cracking stage is W / 3 for M(T) type specimens, where W is the specimen width as defined in the ASTM E561-20 standard.
[0020] It should be pointed out that the width of the test specimens used in the toughness test can have a substantial effect on the R-curve calculated in the test. Since the fuselage sheets are large panels, only toughness results obtained on sufficiently large specimens, such as specimens with a width of 400 mm or more, are deemed meaningful for the evaluation of toughness. For this reason, only test specimen CCT760 with a width of 760 mm was used for the evaluation of toughness. The length of the initial crack is 2ao=253 mm.
[0021] Unless otherwise stated, the definitions of the EN 12258 standard apply. Here, "structural element" or "structural element" of a mechanical structure means a mechanical part whose malfunction may endanger the safety of said structure, its occupants, its users or other people. For aircraft, these structural elements include the structural elements of the fuselage. The structural elements of the fuselage include the elements that make up the fuselage, such as the fuselage skin, the fuselage stiffeners or longerons, the pressurized bulkheads (bulkheads), the fuselage frame (perimeter frame), etc.
[0022] The terms "sheet" or "thin sheet" as used indiscriminately in this disclosure refer to a laminated product having a thickness not exceeding 12.7 mm or 0.5 in. The sheet of the present invention has a thickness of 0.5 to 12.7 mm, preferably 0.5 mm to 9 mm, and more preferably 1.5 mm to 6 mm.
[0023] According to the invention, a selected class of aluminum alloys containing specific and critical amounts of copper, lithium, magnesium, zinc, manganese, but essentially no silver, makes it possible to prepare thin sheets with an improved compromise between toughness and mechanical strength, and an improved value of Δaeff_max, which corresponds to the crack growth at the last effective point of the R-curve.
[0024] A thin sheet less than 12.7 mm thick having an essentially recrystallized grain structure made of an aluminum-based alloy preferably containing, in weight percent, 2.5-3.5% Cu, 0.7-0.9% Li, 0.3-0.5% Mg, 0.2-0.5% Mn, 0.25-0.65% Zn, 0.01-0.15% Ti, 0-0.07% Ag, Fe and Si in an amount not exceeding 0.1% each, and unavoidable impurities with a content not exceeding 0.05% each and not exceeding 0.15% in total, the remainder being aluminum, is in metallurgical state T8, which means that the thin sheet has been solution-treated, cold-deformed and aged.
[0025] The copper content is between 2.5 and 3.5% by weight. If the copper content is more than 3.5% by weight, sufficient toughness cannot be obtained. Preferably, the copper content is at most 3.4%, 3.3%, 3.2% or 3.1%. Below 2.5% the copper content is too low. Preferably, the copper content is at least 2.7% by weight, or even at least 2.8% by weight, in order to obtain sufficient mechanical strength. In an advantageous embodiment of the invention, the copper content is between 2.8 and 3.1% by weight.
[0026] The lithium content is 0.7% to 0.9% by weight. In an advantageous embodiment of the present invention, the lithium content is 0.7% to 0.8%, preferably 0.70 to 0.80%. The addition of lithium can contribute to an increase in mechanical strength and toughness, and if the content is too high or too low, a high toughness value and / or a sufficient elastic limit cannot be obtained.
[0027] The magnesium content is between 0.3% and 0.5% by weight. In an advantageous embodiment of the invention, the magnesium content is between 0.30% and 0.45% by weight, preferably between 0.35% and 0.45% by weight.
[0028] The manganese content is 0.2-0.5 wt%, preferably 0.20-0.45 wt%, and even more preferably 0.25-0.45 wt%. In one embodiment of the present invention, the manganese content is at most 0.45 wt%. The addition of manganese in the claimed amounts allows for the control of an essentially recrystallized grain structure at half thickness while maintaining a homogeneous structure across the thickness.
[0029] The silver content is less than 0.07% by weight, preferably less than 0.05% by weight, even more preferably less than 0.04% by weight, or even less than 0.03% by weight.
[0030] The zinc content is between 0.25 and 0.65% by weight, preferably between 0.45 and 0.65% by weight. According to the invention, it has been observed that the presence of zinc at a content between 0.25% and 0.65% in combination with a silver content of less than or equal to 0.07% by weight, preferably less than or equal to 0.04% or even less than or equal to 0.03%, makes it possible to obtain a higher tensile elastic limit near the ageing peak.
[0031] The titanium content is between 0.01% and 0.15% by weight. Advantageously, the titanium content is at least 0.02% by weight, preferably at least 0.03% by weight. In an advantageous embodiment of the invention, the titanium content is at most 0.1% by weight, preferably at most 0.05% by weight. The addition of titanium contributes to controlling the grain structure, especially during casting.
[0032] The iron and silicon contents are each at most 0.1% by weight. In an advantageous embodiment of the invention, the iron and silicon contents are at most 0.08% by weight, preferably at most 0.04% by weight. The controlled and limited iron and silicon contents contribute to an improved compromise between mechanical strength and resistance to damage.
[0033] Incidental impurities are maintained at a content not exceeding 0.05% by weight each and 0.15% by weight in total, the remainder corresponding to aluminium.
[0034] The alloy composition is substantially free of zirconium. By "substantially free of zirconium," it should be understood that zirconium is not an intentionally added additive. However, zirconium may be present as an impurity in an amount of 0.05% by weight or less, preferably 0.04% by weight or less, even more preferably 0.03% by weight or less, or even 0.01% by weight or less.
[0035] The thin sheet according to the invention is of temper T8 and has: a plane strain toughness Kapp, measured in the LT and TL directions, of at least 120 MPa√m, preferably at least 125 MPa√m and even more preferably at least 130 MPa√m, measured on a CCT760 type test specimen with a precrack 2ao equal to 253 mm; - a tensile elastic limit R measured in the L-direction and the TL-direction of at least 380 MPa, preferably at least 385 MPa p0.2 , an effective value of Δaeff_max, measured in the LT and TL directions, of at least 80 mm, preferably 90 mm, even more preferably 100 mm, the value being measured on a CCT760 type test specimen with a pre-crack 2ao equal to 253 mm.
[0036] The method of manufacturing the sheet according to the present invention includes the steps of melting, casting, rolling, solution treating, quenching, controlled stretching and ageing.
[0037] In a first step, a liquid metal bath is prepared so as to obtain an aluminum alloy of the composition according to the invention, which is then cast in the form of a rolled plate.
[0038] The rolled plate is then homogenized at a temperature between 480° C. and 535° C., preferably between 490° C. and 530° C. and preferably between 500° C. and 520° C. The homogenization time is preferably between 5 and 60 hours. Within the scope of the present invention, if the homogenization temperature is too low or if homogenization is absent, it is not possible to achieve improved isotropic properties compared to those of known products, in particular in terms of mechanical strength in the L and TL directions and toughness for the LT and TL directions, and over this entire thickness range.
[0039] After homogenization, the rolled plate is generally cooled to ambient temperature and then preheated for hot deformation, preferably to reach a temperature of 400-500°C that allows deformation by hot rolling.
[0040] Hot rolling and optionally cold rolling is carried out to obtain a sheet having a thickness of less than 12.7 mm, preferably between 0.5 and 9 mm.
[0041] Advantageously, during hot rolling, a temperature above 400° C., preferably above 450° C., is maintained up to a thickness of 20 mm. Optionally, an intermediate heat treatment during and / or after rolling can be carried out. However, preferably, the method does not include an intermediate heat treatment during and / or after rolling.
[0042] The sheet thus obtained is then solution-treated by heat treatment, preferably for 5 minutes to 2 hours, at 450-535°C, preferably 490°C-530°C and preferably 500°C-520°C, and then quenched. Advantageously, the solution treatment lasts at most 1 hour in order to minimize surface oxidation. It is known to the skilled person that the exact conditions of the solution treatment must be selected depending on the thickness and composition in order to bring the hardening elements into solid solution.
[0043] The sheet is then subjected to cold deformation in controlled tension with a permanent deformation of 0.5-5%, preferably 1-3%. Known steps such as rolling, flattening, smoothing, straightening, forming, etc., can optionally be carried out after solution treatment and quenching and before or after controlled tensioning, but the total cold deformation after solution treatment and quenching should remain below 15%, preferably below 10%.
[0044] Aging is carried out at a temperature of 130 to 170° C., preferably 150 to 160° C., for 5 to 100 hours, preferably 10 to 40 hours.
[0045] Advantageously, an equivalent time at 150° C. of between 10 hours and 80 hours, preferably between 40 hours and 75 hours, and even more preferably between 55 hours and 75 hours.
number
[0046] Equivalent Time
number
number
[0047] The metallurgical condition of the thin sheet at the end of ageing is preferably T8 temper.
[0048] In another embodiment, after the controlled tensile cold deformation step, a short treatment according to the disclosure of EP 2766503 can be carried out to improve the formability of the product. After deformation, the sheet undergoes a final ageing T8.
[0049] The use of the thin sheets according to the invention or obtained according to the method of the invention is advantageous in structural elements of fuselages or in aerospace applications such as in the manufacture of rockets. EXAMPLES
[0050] [Example 1] Alloy D, the composition in weight percent of which is given in Table 1, was cast in plate form. Composition D corresponds to the composition according to the invention.
[0051] [Table 1]
[0052] The two plates were homogenized at 508°C for 12 hours, then heated and hot rolled at 505°C for about 28 hours to obtain two thin sheets with thicknesses of 4.2 mm and 2.5 mm, respectively. The sheets were then subjected to solution treatment at 505°C, stress relief in tension of 2% and ageing at 155°C for 40 hours (equivalent time of 63 hours at 150°C).
[0053] The processing parameters are given in Table 2 below.
[0054] [Table 2]
[0055] The grain structure of the samples at half thickness was characterized from microscopic observation of the metallographic surface in L-TC direction after anodization under polarized light. The grain structure of the sheet is essentially recrystallized at half thickness.
[0056] The samples were mechanically tested to determine their static properties (Table 3) as well as their toughness (Tables 4 and 5). The toughness properties were measured at maximum thickness and after surface scraping to obtain 1.2 mm specimens, where surface scraping was performed on one side only; the width of the specimens is 760 nm. Table 5 discloses the Δaeff_max for each case. Δaeff_max represents the crack extension at the end point of the R-curve, valid according to the ASTM E561-20 standard. The end point is obtained at the time of abrupt fracture of the specimen or, in some cases, at the time when the stress on the uncracked ligaments exceeds the elastic limit of the material on average. The tensile elastic limit R of the material p0.2 The values of are displayed in Table 4; they are measured after the R-curve test on the undeformed zone of the toughness specimen CT760 located above the initial crack.
[0057] [Table 3]
[0058] [Table 4]
[0059] [Table 5]
[0060] [Example 2] Alloys A, B, C, and D were cast into plate form. Their compositions in weight percent are listed in Table 6. Alloys A, B, and C have compositions outside the scope of the present invention. These alloys represent the disclosure of WO 2016 / 051099.
[0061] [Table 6]
[0062] These plates were homogenized, hot rolled, solution treated, and then stretched to obtain thin sheets A#1, B#1, C#1, and D#1 with a thickness of 4.2 mm. The processing conditions are listed in Table 7. All sheets have an essentially recrystallized structure at half thickness.
[0063] [Table 7]
[0064] The aging kinetics was carried out for each sheet at 155°C (Table 8). Figure 1 shows the tensile elastic limit R in the direction of TL as a function of the time (in hours) of aging at 155°C. p0.2 This shows the change in
[0065] [Table 8]
[0066] Sheet D#1 has a higher elastic limit R than the other sheets A#1, B#1, and C#1. p0.2 It can be seen that the hardening kinetics is faster at the beginning of the ageing kinetics.
[0067] [Example 3] Alloys A, E, and F were cast into plate form. Their compositions in weight percent are listed in Table 9. Alloys A, E, and F have compositions outside the scope of the present invention. Alloy A represents the disclosure of WO 2016 / 051099.
[0068] [Table 9]
[0069] These plates were homogenized, hot rolled, solution treated and then stretched to obtain thin sheets with thicknesses of 4 mm, 4.2 mm, 2 mm or 2.5 mm, as the case may be. The processing conditions are shown in Table 10. The sheets were subjected to aging to have a condition close to the aging peak.
[0070] [Table 10]
[0071] All sheets have an essentially recrystallized structure at half thickness. As in Example 1, the sheets were characterized to measure toughness (Table 11) and effective value of Δaeff_max in specimen CCT760.
[0072] [Table 11]
[0073] FIG. 2 shows that alloy D according to the present invention has superior R p0.2 This shows that there is a compromise between strength and toughness.
[0074] FIG. 3 shows that alloy D according to the present invention has superior R p0.2 It is shown that there is a compromise between Δaeff_max and
Claims
1. In weight percent, 2.5 to 3.5% Cu, 0.7 to 0.9% Li, 0.3 to 0.5% Mg, 0.2 to 0.5% Mn, 0.25 to 0.65% Zn, 0.01 to 0.15% Ti, 0 to 0.07% Ag, Fe and Si in an amount of 0.1% or less each, and unavoidable impurities in a content of 0.05% or less each and 0.15% or less in total, the balance being aluminum. A thin sheet having an essentially recrystallized grain structure made of an aluminum-based alloy and having a thickness of less than 12.7 mm.
2. 2. A thin sheet according to claim 1, having a silver (Ag) content of less than or equal to 0.05% by weight, preferably less than or equal to 0.04% by weight, and even more preferably less than or equal to 0.03% by weight.
3. 3. The thin sheet according to claim 1, wherein the magnesium Mg content is between 0.30% and 0.45% by weight.
4. A thin sheet according to any one of claims 1 to 3, characterized in that the lithium Li content is between 0.7% and 0.8% by weight, preferably between 0.70 and 0.80% by weight.
5. 5. The thin sheet according to claim 1, wherein the copper (Cu) content is between 2.8 and 3.1% by weight.
6. A thin sheet according to any one of the preceding claims, in which the manganese (Mn) content is between 0.20 and 0.45% by weight, preferably between 0.25 and 0.45% by weight.
7. 7. The thin sheet according to claim 1, wherein the zinc (Zn) content is between 0.45% and 0.65% by weight.
8. In quality T8, a plane strain toughness Kapp in the LT and TL directions, measured on a CCT 760 type test specimen with a precrack 2ao equal to 253 mm, of at least 120 MPa√m, preferably at least 125 MPa√m and even more preferably at least 130 MPa√m; - a tensile elastic limit R in the L and TL directions of at least 380 MPa, preferably at least 385 MPa p0.2 and, an effective value of Δaeff_max of at least 80 mm, preferably 90 mm and even more preferably 100 mm, measured in the LT and TL directions on a CCT 760 type test specimen with a precrack 2ao equal to 253 mm; 8. The thin sheet of claim 1 , having
9. A method for producing a thin sheet having a thickness of less than 12.7 mm, preferably a thickness of 0.5 to 9 mm, comprising the steps of: a) in weight percent, 2.5 to 3.5% Cu, 0.7 to 0.9% Li, 0.3 to 0.5% Mg, 0.2 to 0.5% Mn, 0.25 to 0.65% Zn, 0.01 to 0.15% Ti, 0 to 0.07% Ag, Fe and Si in an amount of 0.1% or less each, and unavoidable impurities in a content of 0.05% or less each and 0.15% or less in total, the balance being aluminum. preparing a liquid metal bath to obtain an aluminum alloy; b) casting a plate from said liquid metal bath; c) homogenizing the plate at a temperature between 480°C and 535°C; d) rolling said plate by hot rolling and optionally cold rolling into a sheet having a thickness of less than 12.7 mm, preferably between 0.5 mm and 9 mm; e) subjecting said sheet to solution treatment at a temperature between 450°C and 535°C and quenching; f) subjecting the sheet to controlled tension with a permanent deformation of 0.5-5%; g) carrying out an ageing process which involves heating at a temperature of 130-170° C., preferably 150-160° C., for a period of 5-100 hours, preferably 10-60 hours; Manufacturing method.
10. The aging carried out in step g) is performed according to the following formula: [0010] An equivalent time of 10 hours to 80 hours, preferably 40 hours to 75 hours, calculated at a temperature of 150° C. according to [0025] having T in the ceremony ℃ (t) (in °C) is the instantaneous temperature of the sheet changing with time t (in seconds); A method for producing the thin sheet according to claim 9.
11. Use of a sheet according to any one of claims 1 to 8 or obtained according to claim 9 or 10 for a structural element of a fuselage.